PENGARUH KECERDASAN EMOSIONAL DAN LINGKUNGAN BELAJAR TERHADAP PRESTASI MENGHAFAL AL-QUR’AN SISWA SMP ISLAM AL-AZHAR 4 KEMANDORAN JAKARTA SELATAN - A. M Zuhri Patettengi (LPPM Sekolah Tinggi Agama Islamm (STAI) Fatahillah Serpong, Tangerang Selatan-Banten, Indonesia, 2019)
This study aims to determine the effect of emotional intelligence and learning environment on memorization of memorizing the Koran of Al-Azhar Islamic Middle School 4 students in Kemandoran, South Jakarta. This research is a quantitative study, with a population of all students of class VIII (90 students), and a sample of 74 students. The sampling technique uses a combination of 2 techniques, namely random and proportional techniques. Data collection techniques using questionnaires / questionnaires, documentation and tests. Analysis of the data used is multiple linear regression analysis. The results of this study indicate that: 1) There is a positive and significant influence of emotional intelligence on the achievement of memorizing Al-Qur'an at the Al-Azhar Islamic Middle School 4 Kemandoran South Jakarta students; 2) There is a positive and significant influence of the learning environment on the achievement of memorizing al-Qur'an at the Al-Azhar Islamic Middle School 4 Kemandoran South Jakarta students; 3) There is a positive and significant influence of the interaction of emotional intelligence and the environment on the achievement of memorizing the Qur'an at the Al-Azhar Islamic Middle School 4 Kemandoran Jakarta Selatan students.